Analysis of the Influence of Tread Pattern on Tire Grip on Road Surface - Witoni Witoni; I Surya; L Vectra (International Conference on Engineering and Technology Development (ICETD), 2017)
The role of tires on motor vehicles is very important, and very useful for reducing vibrations caused by road surface. Tires are the components of a vehicle that is in direct contact with the road. When we are driving a vehicle, the tires will also protect the wheel from wear and damage, as well as provide stability between the vehicle and the condition of the road surface to increase speed and facilitate the movement or friction between the tire with the road surface. Tires are one component of a vehicle that has a very vital function, in addition to controlling direction of the vehicle tires also functioned as penaggung vehicle weight including passengers it greatlyaffects the stability and performance of the tire during use so that the required accuracy in the selection of tires for vehicles. The study entitled "Analysis of theEffect of Shape traction Tread Pattern Of Ban On Asphalt Road Surface", formulated problem of how to influence the form of the tread pattern of thetire grip on the asphalt road and fuel consumption on a motorcycle. The purpose of this study was to determine the effect of the tread pattern of the tire grip on the asphalt surface and determine how much influence the fuel consumption in the engine capacity of 110cc motorcycles bertrasmisi manual. This study uses a friction test on the tread pattern to the conduct performed by the run the vehicle up to speed past a predetermined total braking. Based on the analysis carried actual data, obtained the conclusion that the effect of the tread pattern using the same two types of tire that is bias-type braking distance cruiser get good results and stable use se30 corsa tires compared with nr72 irc tires.